Nucleus accumbens core and pathogenesis of compulsive checking. Issue 1 (February 2015) - Ballester González, Javier; Dvorkin-Gheva, Anna; Silva, Charmaine; Foster, Jane A.; Szechtman, Henry
Abstract : To investigate the role of the nucleus accumbens core (NAc) in the development of quinpirole-induced compulsive checking, rats received an excitotoxic lesion of NAc or sham lesion and were injected with quinpirole (0.5 mg/kg) or saline; development of checking behavior was monitored for 10 biweekly tests. The results showed that even after the NAc lesion, quinpirole still induced compulsive checking, suggesting that the pathogenic effects produced by quinpirole lie outside the NAc. Although the NAc lesion did not prevent the induction of compulsive checking, it altered how quickly it develops, suggesting that the NAc normally contributes toward the induction of compulsive checking. Saline-treated rats with an NAc lesion were hyperactive, but did not develop compulsive checking, indicating that hyperactivity by itself is not sufficient for the pathogenesis of compulsive checking. It is proposed that compulsive checking is the exaggerated output of a security motivation system and that the NAc serves as a neural hub for coordinating the orderly activity of neural modules of this motivational system. Evidence is considered suggesting that the neurobiological condition for the pathogenesis of compulsive checking is two-fold: activation of dopamine D2/D3 receptors without concurrent stimulation of D1-like receptors and long-term plastic changes related to quinpirole-induced sensitization.